Dysregulation of NK and CD8+T Cells by the Microbiota Promotes the Progression of Lung Cancer - Shouxin Hu; Yanfang Zha; Wenwen Yang; Kele Cui; Min Cheng (Journal of Immunology Research)
The commensal microbiota is involved in maintaining local pulmonary immune homeostasis under physiological conditions. Alterations in the amount and dominant species of the microbiota can reshape the immune response of the body and lead to a variety of lung diseases, including cancer. The precise mechanisms by which microbiota regulate immune cells during the progression of lung cancer remain obscure. In this study, using a Kras-mutated-driven spontaneous lung cancer mouse model, we found that the depletion of microbiota can alleviate lung lesions in Kras-mutated mice at different stages of tumour development. Long-term antibiotic treatment significantly reduced the number NK cells and IFN-γ secretion and CD8+T cells in the lungs of wild-type (WT) mice, suggesting that the microbiota plays an important role in maintaining homeostasis of NK cells and CD8+T cells under normal conditions. However, in Kras-mutated mice, the altered pulmonary immune microenvironment resulted in a microbiota disorder and in the loss of the ability to regulate the immune responses of NK cells and CD8+T cells, thus promoting the occurrence and development of lung cancer. Further mechanistic studies have shown that the CXCL9-CXCR3 axis participated in the local recruitment of NK cells and CD8+T cells by the microbiota into lung tissues in Kras-mutated mice. Our findings reveal the role of the microbiota in reshaping tumour-related immune responses involving NK cells and CD8+T cells and shed light on the clinical immunotherapy of lung cancer.